2016
DOI: 10.1097/md.0000000000004057
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of sutures coated with triclosan for the prevention of surgical site infection after elective colorectal surgery according to the PRISMA statement

Abstract: Background:Several randomized clinical trials (RCTs) conducted to evaluate the effect of triclosan-coated suture on surgical site infection (SSI) yield to controversial results. The primary purpose of this systematic review and meta-analysis was to analyze the available RCTs, comparing the effect of triclosan-coated suture with uncoated suture on the incidence of SSI after elective colorectal operations. As secondary endpoint of the analysis, we considered length of hospital stay after surgery.Methods:We perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 41 publications
2
15
1
Order By: Relevance
“…There have been 11 previous reviews in this topic area, the results of these reviews have been summarised in table 2 27 28 30–32 58–63. Our results support the findings of Konstantelias et al who concluded that triclosan-coated sutures were associated with a significantly lower risk of SSI when compared with standard sutures 32 61.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…There have been 11 previous reviews in this topic area, the results of these reviews have been summarised in table 2 27 28 30–32 58–63. Our results support the findings of Konstantelias et al who concluded that triclosan-coated sutures were associated with a significantly lower risk of SSI when compared with standard sutures 32 61.…”
Section: Discussionsupporting
confidence: 86%
“…de Jonge et al reported a meta-analysis of 21 RCTs including 6462 patients, also concluding that triclosan-coated sutures significantly reduced the risk of SSI compared with standard sutures 32. Five out of 11 reviews included a risk of bias assessment27 31 32 59 63 and only one review assessed the quality of evidence using the GRADE criteria 59…”
Section: Discussionmentioning
confidence: 99%
“…Nine meta-analyses were identified from database searching [28,29,[33][34][35][36][37][38][39] (Table 2). After the critical appraisal of all publications, Henriksen et al was selected as the latest meta-analysis that best matched the inclusion and exclusion criteria [28].…”
Section: Clinical Resultsmentioning
confidence: 99%
“…The sample size is estimated on the basis of a two-sided chi 2 test for equality of the proportions of SSI occurrence within 30 days in the treatment and control groups (null hypothesis). Based on evidence in the literature, an infection rate of 12% is assumed for the control group and it is expected that the use of antibacterial sutures will reduce the SSI rate to 4% in the treatment group [11, 12].…”
Section: Methodsmentioning
confidence: 99%